Penyeluhan Literasi Keuangan Rumah Tangga Istri Nelayan Kelurahan Guraping Kecamatan Oba Utara Kota Tidore Kepuluan - Johan fahri; Hartaty Hadady; Musdar Muhammad (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Women (fishermen's wives) in the coastal community of Guraping Village, North Oba District, Tidore Islands City play a very important role in maintaining the survival of their households. Because it often happens that the husband's source of income as the head of the family is relatively little. using methods; FDG, lectures, training and monitoring, The target of service activities is to fishermen's wives to manage good and healthy household finances. The output of this dedication is published in service journals, videos and online or print media. Results: held on Sunday, August 13, 2023, at the Guraping sub-district office office in North Oba district, the post-graduate PKM activity will be carried out at noon at 13.00 Wit until it is completed. The participants who attended for this PKM activity were 25 people consisting of fishermen's wives and young men from Guraping. Given the importance of women's role in the household, it is important to know the contribution made by women to meet their household needs.